Mapping strain modulated electronic structure perturbations in mixed phase bismuth ferrite thin films1. Issue 8 (28th February 2015) - Krishnan, P. S. Sankara Rama; Aguiar, Jeffery A.; Ramasse, Q. M.; Kepaptsoglou, D. M.; Liang, W.-I.; Chu, Y.-H.; Browning, N. D.; Munroe, P.; Nagarajan, V.
<x xml:space="preserve">Abstract</x> A combination of atom column-by-column scanning transmission electron microscopy and density functional theory shows how epitaxial strain alters the local electronic structure in mixed phase bismuth ferrite thin films.